Impact of low-x resummation on QCD analysis of HERA data - Abdolmaleki, Hamed; Britzger, Daniel (The European physical journal. C, Particles and fields, 2018)
Fits to the final combined HERA deep-inelastic scattering cross-section data within the conventional DGLAP framework of QCD have shown some tension at low x and low Q2Q2Q^2. A resolution of this tension incorporating ln(1/x)ln⁡(1/x)\ln (1/x)-resummation terms into the HERAPDF fits is investigated using the xFitter program. The kinematic region where this resummation is important is delineated. Such high-energy resummation not only gives a better description of the data, particularly of the longitudinal structure function FLFLF_L, it also results in a gluon PDF which is steeply rising at low x for low scales, Q2≃2.5GeV2Q2≃2.5GeV2Q^2 \simeq 2.5\,\hbox {GeV}^2, contrary to the fixed-order NLO and NNLO gluon PDF.
Gesehen am10.07.2020